Women Radicalization in the Arab World - Al-Badayneh, Diab M.; Khelifa, Maher; Elwakad, Amr (Migration Letters, 2024)
The study explores the drivers of radicalization among females from 12 Arab states (Kuwait, UAE, Oman, KSA, Qatar, Bahrain, Jordan, Morocco, Tunisia, Libya, Lebanon, and Egypt). A sample of 2624 young female students was selected, of whom 11.7% were expatriates and 88.3% were citizens. A 44-item questionnaire with relevant scales was used. The instrument has a strong reliability (α=0.96) and a construct validity (LSC and Radicalization Scale) of (r= 0.723, α=0.00). Findings showed that all independent variables combined explained 67% of the variance of female radicalization, and a significant overall impact of independent variables on female’s radicalization (F 214.806 α=0.00). Results showed a uniquely significant contribution of all predictors with the exception of location, father’s work, and religiosity. However, significant differences were found in females’ radicalization attributed to religion, (F=123.932, α=0.000) and residence (citizen vs. Expat) (F=4.349, α=0.03). Security implications such as understanding factors behind women terrorist radicalization and the women’s roles in preventing and countering violent extremism and radicalization were discussed.